OPTIMALISASI PEMANFAATAN PEKARANGAN RUMAH UNTUK MENUNJANG KETAHANAN PANGAN DALAM MENGHADAPI DAMPAK PANDEMI COVID-19 - Herlina, Nina; Hartini, Elya; Ratnaningsih, Nani; Hidayat, Edi (LPPM Univeristas Siliwangi, 2020)
The PbM-KP service activities carried out by the PPM Team with a group of women fromCintaraja Village and Cipakat Village, Singaparna District, Tasikmalaya Regency, is one form ofthe Tri Dharma Perguruan Tinggi task that every lecturer must carry out.The purpose of PbM-KP dedication is to improve the mindset, skills of cultivating organicplants, improve and improve the family economy by seeking the availability of foodstuffs in theiryards, especially in the current Covid 19 pandemic conditions.Activities in the PPM program are socialization and demonstration of planting mediaprocessing, organic fertilizers and aquaponics of mina kale in the cultivation of fish in buckets,caysim / mustard greens, ginger, turmeric and lemongrass, minimizing the impact of a shortage ofspices and protein as a source of family health. Because with this application, food security can beaccelerated more quickly in the community affected by the Covid-19 pandemic.The output to be achieved from this PbM-KP community service activity is in the formof assistance to the family economy, publication of an organic vegetable farming manual in theyard, publication in a journal or national proceeding with ISSN not accredited and publication inthe local print media